2004
DOI: 10.1161/01.cir.0000141593.05085.87
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Aneurysms of the Aortic Root

Abstract: Background-This study evaluated long-term results of aortic root replacement and valve-preserving aortic root reconstruction for patients with aneurysms involving the aortic root. Methods and Results-Two-hundred three patients aged 53Ϯ16 years (meanϮSD; 153 male, 50 female) underwent elective or urgent aortic root surgery from 1971 to 2000 for an aortic root aneurysm: 149 patients underwent a composite valve conduit reconstruction, and 54 patients underwent valve-preserving aortic root reconstruction. Fifty pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(55 citation statements)
references
References 27 publications
5
46
0
4
Order By: Relevance
“…The late mortality of these patients is low, similar to the life expectancy of the general population, as demonstrated previously [17]. Renal failure, being dialytic or not, it is a factor that is invariably associated with higher mortality, either early or late.…”
Section: (42 -80) (Values In Parentheses With a 95% Confidence Intersupporting
confidence: 77%
See 1 more Smart Citation
“…The late mortality of these patients is low, similar to the life expectancy of the general population, as demonstrated previously [17]. Renal failure, being dialytic or not, it is a factor that is invariably associated with higher mortality, either early or late.…”
Section: (42 -80) (Values In Parentheses With a 95% Confidence Intersupporting
confidence: 77%
“…Niederhäuser et al [16], with seven reoperations in 181 patients operated with a valved conduit, did not identify predictors for the need of reoperation. On the other hand, Zehr et al [17] in a series of 203 surgical patients observed that Marfan syndrome, root reconstruction with the aortic valve preservation and the need of associated valvular procedure were significant predictors for necessity of reoperation.…”
Section: (42 -80) (Values In Parentheses With a 95% Confidence Intermentioning
confidence: 99%
“…İlk olarak yapıldığı 1968 yılından beri orijinal teknikte birkaç değişiklik yapılmış olmakla birlikte günümüzde de bütün dünyada yaygın olarak uygulanmaktadır. Yapılan çalışmalara göre assenden aortanın koruyucu ameliyatları ile karşılaştırıldığında, Bentall tekniğinin MFS hastalarında hem reameliyat sayısını azalttığı hem de kısa ve uzun süreli sonuçlarının daha iyi olduğu belirtilmektedir (2) .…”
Section: Marfan Sendromu (Mfs)unclassified
“…Proksimal aortanın ilerleyici olarak genişlemesine bağlı bu komplikasyonlara zaman için-de aort kapak yetmezliği de eklenmektedir. Yapılan son araştırmalara göre; MFS hastalarında yalnızca proksimal aorta replasmanı yerine proksimal aorta ve aort kapak replasmanlarının birlikte yapılması durumunda normal yaşam süreleri elde edilebildiği gibi reameliyat insidansı da azalmaktadır (2) .…”
Section: Introductionunclassified
“…66 The risks associated with descending thoracic aortic repair are 2-fold higher, 67 and those for extensive thoracoabdominal aortic disease are double that. 68 Complications from surgical repair include hemorrhage, postoperative paraplegia from spinal cord ischemia for descending thoracic repair, and stroke from cerebral ischemia during arch repairs.…”
Section: Thoracic Aortic Aneurysmsmentioning
confidence: 99%